2011
DOI: 10.14310/horm.2002.1322
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia during oral glucose tolerance test and high normal serum cortisol are associated with increased secretion of calcitonin in normal subjects

Abstract: ObJEctIVE: Previous studies showed that insulin stimulated directly calcitonin (ct) secretion in the pig thyroid, while dexamethasone stimulated the production of ct and ct mrNA in medullary thyroid carcinoma (Mtc) cell lines. the objective of this study was to investigate if hyperinsulinemia during the oral glucose tolerance test (Gtt) stimulates ct secretion in normal subjects as well as to examine the relationship between serum cortisol and ct. DEsIGN: In 26 normal subjects (9 men and 17 women) with detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Arguably, the clinical studies described here may suffer from methodological issues related to study power and variation in design, but they indicate a relation between calcitonin and insulin in humans. This is supported by the observation that endogenous calcitonin was reported to rise and shown to correlate with insulin levels following 75-g OGTT performed in 26 overweight subjects with normal glucose tolerance (148). More studies designed specifically to evaluate this possible relationship are warranted.…”
Section: Glucometabolic Effectsmentioning
confidence: 84%
“…Arguably, the clinical studies described here may suffer from methodological issues related to study power and variation in design, but they indicate a relation between calcitonin and insulin in humans. This is supported by the observation that endogenous calcitonin was reported to rise and shown to correlate with insulin levels following 75-g OGTT performed in 26 overweight subjects with normal glucose tolerance (148). More studies designed specifically to evaluate this possible relationship are warranted.…”
Section: Glucometabolic Effectsmentioning
confidence: 84%
“…malignancies, thus, it was withdrawn from the market in Europe and Canada (92). Gydesen et al investigated the effect of a dual amylin and calcitonin receptor agonist (DACRA) on rats fed with high-fat diet, showing that this treatment resulted in improved glucose homeostasis, higher weight loss, enhanced insulin action and decreased lipid accumulation in the liver and skeletal muscles, whilst improved food preferences was also noted in these rats (105,106). Finally, Polymeris et al demonstrated that serum calcitonin levels increased after a 75-g oral glucose tolerance test in healthy adults, suggesting that calcitonin may be stimulated by hyperinsulinemia (107).…”
Section: Calcitonin and Nafldmentioning
confidence: 99%
“…But whether this effect has physiological relevance remains to be determined. In a study with 26 subjects, who were mainly overweight but with normal glucose tolerance, there was an increase in serum calcitonin levels after a 75-g oral glucose tolerance test which correlated with insulin levels, suggesting a possible relationship between insulin and calcitonin ( 88 ). This is in concert with the observation that insulin directly stimulates calcitonin release in the perfused pig thyroid gland ( 89 ).…”
Section: Calcitonin In Metabolic Diseasementioning
confidence: 99%